2014
DOI: 10.1016/j.cjca.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The Heart: Mostly Postmitotic or Mostly Premitotic? Myocyte Cell Cycle, Senescence, and Quiescence

Abstract: The concept of myocyte division and myocyte-mediated regeneration has re-emerged in the past five years through development of sophisticated transgenic mice and carbon-dating of cells. Although, recently, a couple of studies have been conducted as an attempt to intervene in myocyte division, the efficiency in adult animals remains discouragingly low. Re-enforcing myocyte division is a vision that has been desired for decades, leading to years of experience in myocytes resistance to pro-proliferative stimuli. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
2
17
0
Order By: Relevance
“…In particular, birth itself triggers innumerable molecular changes as the body transitions from receiving all oxygen and nutrients from the placenta to breathing and eating independently. It is this window of time that cardiomyocytes transition from a proliferative state to a quiescent state [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, birth itself triggers innumerable molecular changes as the body transitions from receiving all oxygen and nutrients from the placenta to breathing and eating independently. It is this window of time that cardiomyocytes transition from a proliferative state to a quiescent state [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that hypertrophic growth is related to upregulation of G1 cyclin or cyclin-dependent kinases, and that postmitotic cardiac myocytes reenter the cell cycle for proliferative growth (15 , 22 , 23) . To assess how the cell cycle is regulated by cholesterol-induced hypertrophy and reversed by proteasome inhibitors, H9c2 cells were analyzed by flow cytometry assay after treatment with 5 μg/ml cholesterol in the presence or absence of 5 or 50 nM Bortezomib or 5 or 50 nM MG132 for 24 h, followed by staining with propidium iodide.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor suppressor p53 can facilitate cell cycle arrest and senescence program in cells in response to stress [54]. The high expressions of p16 and p53 hamper the resuming cell cycle progression for a senescent cell [55]. Myocyte senescence is associated with oxidative stress, chronic adrenergic signaling, renin-angiotensin-aldosterone signaling (RAAS) and mTORC pathway [55].…”
Section: Discussionmentioning
confidence: 99%
“…The high expressions of p16 and p53 hamper the resuming cell cycle progression for a senescent cell [55]. Myocyte senescence is associated with oxidative stress, chronic adrenergic signaling, renin-angiotensin-aldosterone signaling (RAAS) and mTORC pathway [55]. The mitochondrial functional impairment induces oxidative stress, serves as a primary inciting stimulus for transition into senescence.…”
Section: Discussionmentioning
confidence: 99%